Molecular identification of virulence genes in laboratory strains streptococcus pneumoniae / Yuhaniz Atiqah Nor Azlan - Nor Azlan, Yuhaniz Atiqah (2015)
Streptococcus pneumonia is the main cause of pneumococcal diseases ranging from non-invasive condition of otitis media and sinusitis to more invasive conditions of meningitis and septicemia particularly in children, elderly and immunocompromised. Virulence genes found in Streptococcus pneumoniae are lytA, ply, PsaA, PspA, cbpA, PavA, nanA, nanB, eno, and psrP. There is limited information about the distribution of virulence genes in Streptococcus pneumoniae isolates from laboratory strains Streptococcus pneumoniae in comparison with clinical strains. Therefore, this study was conducted to detect virulence genes (lytA, ply, PsaA, PspA, cbpA, PavA, nanA, nanB, eno, and psrP) and to compare the virulence genes distribution in Streptococcus pneumoniae from laboratory reference strains with clinical strains. A sample Streptococcus pneumoniae (ATCC 6305) from laboratory strains was obtained from Microbiology laboratory, UiTM Puncak Alam and the bacterial DNA was extracted using the boiling method. The detection of lytA, ply, PsaA, PspA, cbp A, PavA, nanA, nanB, eno, and psrP in Streptococcus pneumoniae from laboratory reference strains was done using SYBR Green real-time PCR. In this study, the biochemical and molecular tests confirmed the isolates as Streptococcus pneumoniae (ATCC 6305). The real-time PCR showed that all isolates were positive for virulence genes LytA, Ply, NanB and PspA genes. No amplification was seen for PsaA, cbpA, PavA, nanA, eno and psrP genes. Hence, this study indicates that, with such genotypic distribution pattern, Streptococcus pneumoniae from laboratory strains is a less pathogenicity as only four virulence genes detected compared with virulence gene's presence in the clinical strains. The application of real-time PCR proved a rapid and specific method for the detection of virulence genes in Streptococcus pneumoniae.